5-Lap Run Weight Loss Achievement - Apriandi, Dirzal; Wati, Isti Dwi Puspita; Salacup, Vince Louisse D. (CV Media Inti Teknologi, 2024)
A condition known as dehydration occurs when the body lacks fluid and experiences problems with its metabolic functions. The study provides the impact of dehydration on running 5 laps at GOR SSA PONTIANAK by comparing weight loss before and after running. The research method was experimental, with a sample of 16 students. Performed with the measurement procedure of the 5 lap running test, and body weight before and after running. The results showed there was a decrease in body weight with an average decrease of 0.78 grams, this figure is equivalent to approximately 5% of fluid levels in the body assuming fluid in the body is 60%-70% of body weight. Weight loss of up to 2% is statistically insignificant, but physiologically this is the recommended limit of weight loss in one exercise.